Could inflammation contribute to salivary gland dysfunction in patients with chronic heart failure? - Klimiuk, Anna; Zalewska, Anna; Knapp, Małgorzata; Skutnik-Radziszewska, Anna; Maciejczyk, Mateusz (Frontiers in Immunology, 2022)
Heart failure (HF) is one of the leading causes of death worldwide. HF results not only in cardiovascular dysfunction, but also numerous pathologies in the oral cavity and salivary glands. The present study is the first to evaluate whether salivary inflammatory and anti-inflammatory factors may be related with the occurrence of hyposalivation in HF patients. We also evaluated the potential of salivary biomarkers in the diagnostics of HF. The study included 30 women with HF and 30 sex- and age-matched healthy controls. We demonstrated significantly higher levels of pro-inflammatory cytokines, anti-inflammatory cytokines, Th1, Th2, Th17, chemokines and growth factors in unstimulated saliva of HF patients compared to controls. However, the results do not indicate dominance of either branch of the immune response. The concentration of selected biomarkers is significantly higher in patients with HF and salivary gland dysfunction compared to patients with normal saliva secretion and healthy subjects (IL-1β, TNF-α, IL-7, IL-13, INF-γ, IL-12, IL-15, IL-5, IL-6, IL-9, IL-17, MCP-1/CCL-2, EOTAXIN/CCL11, RANTES/CCL5, GM-CSF, VEGF, FGF basic, PDFG-BB). Multivariate regression analysis showed that the content of salivary cytokines, chemokines and growth factors is highly dependent on salivary gland function, i.e. salivary flow rate, total protein content and amylase activity. Using receiver operating characteristic (ROC) analysis, we showed that salivary TNF-α, INF-γ, IL-12 and EOTAXIN/CCL11 differentiated patients with HF and hyposalivation with the highest sensitivity and specificity compared to patients with normal salivary secretion and controls. Interestingly, the content of some pro- and anti-inflammatory mediators in saliva significantly exceeds their concentration in plasma. In addition, salivary biomarker levels do not reflect their plasma content, which may suggest a different nature/severity of inflammatory changes at the central (blood) and local (salivary) levels. Although our study was purely observational, the significantly higher concentration of inflammatory parameters in saliva compared to plasma, as well as the lack of saliva-blood correlation, may suggest increased production/secretion of these compounds in salivary cells of HF patients. ROC analysis did not confirm the diagnostic utility of salivary cytokines and chemokines in the differential diagnosis of HF patients.